EFFECT OF PROFITABILITY, AND SALES GROWTH, WITH THE CONTROL VARIABLE ASSET STRUCTURE ON CAPITAL STRUCTURE IN VARIOUS INDUSTRY SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2014-2018 - Vincentia Wahju Widajatun; Karlina Fitrahelsia Suhenri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The goal of this study is to decide if the Asset Structure control variable has a major impact on the capital structure on profitability and sales growth. This type of research is explanatory research with a quantitative approach method. The data in this analysis are secondary data obtained through the website of the Indonesia Stock Exchange and the website of the Indonesia Finance Market: Indonesia Stock Exchange. All the various industries sector companies listed on the Indonesia Stock Exchange for the period 2014-2018 were the population in this study. Although the sample for this analysis was determined by the purposeful method of sampling in which 23 companies were chosen. Documentation analysis and literature study were the data collection methods used. The analysis technique used is descriptive statistical analysis, panel data regression, classical assumption test, and hypothesis testing. The results showed that there was a simultaneous influence on the variable profitability and sales growth, as well as the control variable of asset structure on capital structure. Although the study results partly indicate. Although earnings growth does, this profitability does not have a major effect on the capital structure and the control variable asset structure has a negative and significant impact on the capital structure.